A clinical study of generalised peritonitis and its management in a rural setup - Shanker, M. R.; Nahid, M.; S., Prajwal (International Surgery Journal, 2018)
Background: Generalised Peritonitis is a common surgical emergency and its treatment remains a challenge despite advances in surgical techniques, antimicrobial therapy and intensive care support. The commonest etiological factors are perforation of hollow viscus and appendicitis. The aim was to study the most common cause of perforation peritonitis, associated risk factors, modes of clinical presentation, management, postoperative complications, and comorbid conditions influencing the morbidity and mortality in rural set up. Methods: 50 patients of peritonitis of over 10 years of age managed in our institution from July 2015 to November 2016 were studied and followed up on a three-monthly basis for a period varying from 12 months to 2 years with an average of 18 months. Results: Appendicular perforation was the most common cause of peritonitis followed by peptic ulcer perforation. Perforation peritonitis constituted 26% of total emergency operations performed with a male to female ratio of 2.84:1 and age between 41-50 years. Patients presenting within 24 hours of perforation had an uneventful recovery whereas those presenting after 24 hours had significant postoperative complications. The serum CRP levels provided as good prognostic marker. It remained high in complicated cases. Out of 56% complication rate, wound infection was the commonest. Conclusions: Early diagnosis and surgical intervention plays a crucial role in early recovery, though the end result depends on many factors like age of the patient, degree of peritoneal contamination and presence of comorbid diseases. This study also highlights the role of CRP as a serum prognostic marker.